Covalent association of C3b with C4b within C5 convertase of the classical complement pathway (The Rockefeller University Press, 1987)
The C5 convertase of the classical complement pathway is a complex enzyme consisting of three complement fragments, C4b, C2a, and C3b. Previous studies have elucidated functional roles of each subunit (4, 6, 7), but little is known about how the subunits associate with each other. In this investigation, we studied the nature of the classical C5 convertase that was assembled on sheep erythrocytes. We found that one of the nascent C3b molecules that had been generated by the C3 convertase directly bound covalently to C4b. C3b bound to the alpha' chain of C4b through an ester bond, which could be cleaved by treatment with hydroxylamine. The ester bond was rather unstable, with a half- life of 7.9 h at pH 7.4 and 37 degrees C. Formation of the C4b-C3b dimer is quite efficient; e.g., 54% of the cell-bound C3b was associated with C4b when 25,000 molecules of C4b and 12,000 molecules of C3b were present per cell. Kinetic analysis also showed the efficient formation of the C4b-C3b dimer; the rate of dimer formation was similar to or even faster than that of cell-bound monomeric C3b molecules. These results indicate that C4b is a highly reactive acceptor molecule for nascent C3b. High-affinity C5-binding sites with an association constant of 2.1 X 10(8) L/M were demonstrated on C4b-C3b dimer-bearing sheep erythrocytes, EAC43 cells. The number of high- affinity C5-binding sites coincided with the number of C4b-C3b dimers, but not with the total number of cell-bound C3b molecules. Anti-C4 antibodies caused 80% inhibition of the binding of C5 to EAC43 cells. These results suggest that only C4b-associated C3b serves as a high- affinity C5 binding site. EAC14 cells had a small amount of high- affinity C5 binding sites with an association constant of 8.1 X 10(7) L/M, 100 molecules of bound C4b being necessary for 1 binding site. In accordance with the hypothesis that C4b-associated C4b might also serve as a high-affinity C5-binding site, a small amount of C4b-C4b dimer was detected on EAC14 cells by SDS-PAGE analysis. Taken together, these observations indicate that the high-affinity binding of C5 is probably divalent, in that C5 recognizes both protomers in the dimers. The high- affinity binding may allow selective binding of C5 to the convertase in spite of surrounding monomeric C3b molecules.